Subliminal visual stimulation produces behavioural oscillations in multiple frequencies in a visual integration task - Michelle Johannknecht; Alfons Schnitzler; Joachim Lange (Scientific Reports)
Abstract We perceive our surrounding as a continuous stream of information. Yet, it is under debate, whether our brain processes the incoming information continuously or rather in a discontinuous way. In recent years, the idea of rhythmic perception has regained popularity, assuming that parieto-occipital alpha oscillations are the neural mechanism defining the rhythmicity of visual perception. Consequently, behavioural response should also fluctuate in the rhythm of alpha oscillations (i.e., at ~ 10 Hz). To test this hypothesis, we employed a visual integration task. Crucially we investigated if a subliminal stimulus preceding the target stimulus modulates behaviour. Our results show that behaviour fluctuates as a function of delay between subliminal and target stimuli. These fluctuations were found in the range of theta, alpha and beta oscillations. Our results further support the idea, that alpha oscillations are a functional rhythm for visual perception, leading to rhythmic fluctuations of perception and behaviour. In addition, other frequencies seem to play a role for temporal perception.